Comparative Analysis of Grid Fragility Indices in the Nigerian Transmission Network - Oluseyi, P. O.; Ajekigbe, T. O.; Babatunde, O. M.; Akinbulire, T. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
The grid fragility is a prevalent challenge in Nigeria electricity supply industry (NESI).  It has resulted in recorded incidents of voltage collapse which have been on the increase in the recent time. Meanwhile to evaluate this events; thus the nexus between voltage collapse and network capacity was explored. To actualize this, the load flow analysis was carried out on the Nigeria-31 bus system with the aid of the Newton-Raphson iteration technique. Using the relevant parameters (such as bus voltage magnitude, bus voltage angle, generated power, injected power as well as load magnitude) obtained from the analysis, the line stability index and line stability factor were obtained for every line in the network. It was discovered from the values of line stability index that Lines (26-2); (31-7); (10-11); (24-10) and (18-12) are weak and fragile while for the  line stability factor, the values obtained for Lines (10-8); (11-8); (11-10); (24-10) and (18-12) indicate the fragility of some of the lines in the Nigerian Transmission Network.  From this, it was established that the weakest lines were those whose values range from 0.3051 to 0.8813 for the line stability index. Correspondingly; any line that takes the value between 0.2737 and 0.9924 in respect of the line stability factor was also marked as the weakest lines in the network. Thus it was noticed that for the two line stability indices (i.e. stability factor and stability index); Line (11-10) i.e. from Oshogbo to Ikeja-West bus is the most fragile line in Nigeria-31 bus transmission network while the nearest to it are lines (24-10) i.e. from Ayede to Ikeja-West bus and  (12-18) i.e. from Kaduna to Kano bus. This study is potentially sufficient for determining the lines in the transmission network that require utmost consideration for reinforcement in respect of the transmission expansion planning schemes.